Implementation of English Language Learning in Stimulating Early Childhood Roughness Skills - Aninda Tusyifa Faridatu Rohmah; Sri Setyowati; Mallevi Agustin Ningrum; Yes Matheos Lasarus Malaikosa (Sekolah Tinggi Agama Islam Kuningan, 2026)
This study aims to capture how English language learning is applied to stimulate early literacy skills, particularly the early reading and listening skills of children aged 4–5 years. Using a qualitative case study design, this study collected data from the principal, classroom teachers, and students as the primary subjects. Through non-participant observation, in-depth interviews, and documentation, the collected data were then analyzed using Miles and Huberman's interactive analysis model. Field findings indicate that English learning is structured through the English Super Safari program and interaction sessions with native speakers. The methods used are varied, ranging from Total Physical Response (TPR) and Communicative Language Teaching (CLT) to storytelling and game-based learning. The stimulation process is reinforced by the use of interactive visual media, such as flashcards and Smart TVs, which have been proven effective in helping children recognize letter symbols and phonetic pronunciation. The results showed positive developments in children's ability to distinguish letter shapes and respond spontaneously to spoken English instructions without the need for translation. This study concluded that an integrative and enjoyable foreign language introduction can provide a solid foundation for early childhood basic literacy.